Development of a Social Media Branding Model for Marketing Consultancy: A Study on Content Sharing Practices - Jafari, Parisa; Fakhimiazar, Sirous; Iranzadeh , Soleyman; Budaghi Khajenobar , Hosein (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: The research examines the strategic and tactical aspects of content sharing as a means to enhance visibility, engagement, and brand loyalty in the digital realm, drawing on perspectives from managers and experts in marketing consultancy. Method: Employing a mixed-methods approach, which combines qualitative interviews and quantitative surveys, the study provides insights into current practices, challenges, and opportunities that marketing consultants face in utilizing social media for branding. Findings: Through qualitative analysis, the study identifies key factors influencing successful branding on social media, including the creation of appealing content and strategic interaction with customers. Conclusion: This research contributes to the advancement of knowledge in the field of social media marketing and offers practical recommendations for industry professionals, enabling them to adapt to the dynamic nature of online branding in the digital age. Recommendations are provided for leveraging digital marketing strategies to improve brand image and performance, ultimately aiming to guide businesses in navigating the evolving landscape of social media branding.